Relevansi Teori Pembelajaran Behavioristik, Kognitifistik, Konstruktivistik, dan Humanistik untuk Peningkatan Kualitas Pembelajaran - Rohmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research aims to apply a holistic approach in learning, integrating principles from four main learning theories, namely behavioristic, cognitive, constructivistic, and humanistic. This holistic application is aimed at improving the quality of learning at various levels of education. By combining the key elements of each theory, this approach is expected to provide a more comprehensive and effective learning experience for learners. Research methods involve learning design that integrates key aspects of each theory, as well as data collection through observation, interviews, and analysis of learning outcomes. The results showed that the holistic application of learning theory was able to make a significant contribution to improving the quality of learning, by strengthening behavioral, cognitive, constructivist, and humanistic aspects. The implications of this research can be used as a foundation for the development of more holistic learning strategies, harmonizing the diversity of learning theories to achieve more optimal learning goals.